An oxidatively damaged G-quadruplex/hemin DNAzyme. Issue 12 (17th January 2020) - Wang, Jiawei; Cheng, Mingpan; Chen, Jielin; Ju, Huangxian; Monchaud, David; Mergny, Jean-Louis; Zhou, Jun
Abstract : Oxidative damage of guanine to 8-oxoguanine triggers a partial and variable loss of G-quadruplex/hemin DNAzyme activity and provides clues to the mechanistic origins of DNAzyme deactivation. Abstract : Oxidative damage of guanine to 8-oxoguanine triggers a partial and variable loss of G-quadruplex/hemin DNAzyme activity and provides clues to the mechanistic origins of DNAzyme deactivation, which originates from an interplay between decreased G-quadruplex stability, lower hemin affinity and a modification of the nature of hemin binding sites.